The Role of Digital Transformation in Labor Market Changes: An Econometric Analysis of the Impact of Automation on the Manufacturing Sector - Santika, Rani; Farizki, Rafi (Journal of Applied Econometric, 2025)
Digital transformation is fundamentally changing the landscape of the global labor market, especially in the manufacturing sector that is increasingly adopting automation technology. Developing countries, including Indonesia, face significant challenges in responding to shifting skills needs due to these technological developments. This study aims to analyze in depth the impact of automation on labor market dynamics in the manufacturing sector, focusing on changing patterns of skills demand and their implications for labor productivity and resilience. Using a sophisticated econometric approach, this study utilizes panel data from the manufacturing industry in Indonesia over the past ten years. The analysis was conducted using fixed-effects and multivariate regression methods to assess the relationship between the adoption rate of automation technology and key variables of the labor market, such as changes in skill composition, wage levels, and demand for skilled versus unskilled labor. The results of the analysis show that there is a significant impact of automation in reducing the demand for non-skilled labor, while specialized skills, especially in the field of technology and maintenance, are experiencing an increase in demand. This research provides important insights for the formulation of policies that support the upskilling of the workforce in the face of the digital era, and shows that the sustainability of the manufacturing sector is highly dependent on the adaptation and development of technology-based skills.